Developing Digital Storytelling Based on Indonesian Culture to Enhance Students’ Independent Learning in the Society 5.0 - Yunita; Neneng Sri Lestari (Universitas Islam Negeri Palopo, 2025)
The purpose of this research was to develop a digital storytelling product based on Indonesian cultural heritage (Nusantara) to enhance students’ learning independence in the context of Society 5.0. This study employed a research and development (R&D) design using the Borg and Gall model consists of: research and information gathering, planning, initial product development, initial field testing, product revision, main field testing, main product revision, operational field testing, final product revision, and dissemination and implementation. The product development process included expert validation (media, culture, and language), practicality testing by students, and effectiveness testing using a one-group pre-test and post-test design. The results showed that the product improved substantially after expert revisions, with validation scores increasing from below 60% to above 87%. The practicality test involving 25 students yielded an average practicality score of 82%, categorized as “good.” Effectiveness testing revealed a statistically significant improvement in students' learning independence, with a mean difference of 22.7 points (t = 9.85, p = 0.000) between pre-test and post-test scores.